Direct and Indirect Associations of Empathy, Theory of Mind, and Language with Prosocial Behavior: Gender Differences in Primary School Children. Issue 6 (2nd November 2019) - Longobardi, Emiddia; Spataro, Pietro; Rossi-Arnaud, Clelia
Abstract: The authors examined the contributions of empathic concern, perspective taking, theory of mind (ToM), and receptive language to prosocial behavior in a sample of primary school children between 8 and 11 years old. Results showed that empathic concern, perspective taking, and ToM had direct positive effects on prosocial behavior. Girls exhibited higher levels of empathic concern and prosocial behavior; furthermore, gender moderated the observed associations, as perspective taking and ToM were positively and significantly associated with prosocial behavior in boys but not in girls. Last, two indirect paths were detected: empathic concern partially mediated the relation between perspective taking and prosocial behavior, and receptive language had an indirect effect on prosocial behavior by increasing ToM ability. Implications for understanding the impact of the four social-cognitive skills on children's prosocial development are discussed.